Incidence of Mycobacterium avium Subsp. paratuberculosis (MAP) Infection in slaughtered buffaloes (Bubalus bubalis) of Malwa Region of Madhya Pradesh - Jatav, GP; Garg, UK; Shukla, Supriya; Chabra, Daljeet; Jayraw, AK; Shrivastava, Nidhi; Karmore, SK; Agarwal, Vivek (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was undertaken to assess the incidence of subclinical and clinical paratuberculosis in slaughtered buffaloes of Malwa region of Madhya Pradesh. They were unproductive buffaloes (1- 10 years old) slaughtered in Mhow and Indore examined for subclinical and clinical Mycobacterium avium subsp. paratuberculosis (MAP) infection. Study of gross lesions of intestine and respective mesenteric lymph nodes (MLNs) showed overall 87.33% (131/150) incidence of paratuberculosis. Out of these 131 cases of paratuberculosis, 18.21% (24/131) buffaloes suffered from subclinical and 81.68% (107/131) from clinical paratuberculosis, whereas impression smear examination revealed clinical and subclinical paratuberculosis up to 25.77 and 74.33% in intestine and 13.51 and 86.49% in MLNs, respectively.